Quaternary Prevention for the humanization of Primary Health Care - Dalcanale Tesser, Charles (O Mundo da Saúde, 2012)
We discuss the relationship between the concept and the practice of quaternary prevention and humanization in Brazilian Primary Health Care (PHC), focused in individual clinical care. Some considerations are proposed on the present moment of biomedical care in general and in Brazilian PHC, for contextualizing the meaning of the concept of quaternary prevention. We indicate the incompleteness of the introduction of Brazilian UHS (Unified Health System) and PHC, as well as the quality, many times doubtful, of their care practices, historically degraded and dehumanized, which makes highly relevant quaternary prevention and humanization of care. We point to the main meaning of the concept of quaternary prevention, which is to prevent hypermedicalization of care and to avoid unnecessary interventions, reducing damages, by means of techniques and qualified and personalized care practices. This implements inside professional practices the ethical precept “first, do no harm”, ever repeated in medical discourse. We point to some characteristics of quaternary prevention with an emphasis on its practice, as well as to its imbrications to humanization of care and its relationship to dealing to social medicalization in professional practices, which historically has been favoring uncritically excessive medicalization; and some associated challenges, as well as potentialities and emergent practical ramifications, still only insinuated, such as the use of non-biomedical care resources in quaternary prevention, exemplifying the productivity of this concept and its contribution for the humanization of care in PHC.